A cross sectional survey of secondary prevention measures in patients with peripheral arterial disease in primary care. Issue 983 (6th September 2007) - Dunkley, Alison; Stone, Margaret; Sayers, Robert; Farooqi, Azhar; Khunti, Kamlesh
Abstract : Background: The National Service Framework for coronary heart disease (CHD) defines standards for the secondary prevention of cardiovascular disease in at risk individuals, including those with peripheral arterial disease (PAD). Aim: To assess current standards of secondary prevention and health monitoring in patients with PAD following a vascular procedure, and additionally compare care in patients with and without diagnosed CHD. Methods: Indicators for this cross sectional survey were identified from national recommendations and evidence. A retrospective review was conducted of general practitioner records, for patients who were treated in hospital for PAD. Results: Data were collected for 103 patients from 42 practices. Overall, prescribing was well achieved for antiplatelets but poor for statins. Standards of assessment of blood pressure, smoking status, and smoking cessation advice were high. However, approximately only half of the patients received advice about exercise or had their body mass index checked. Furthermore, for all indicators, standards of care for patients who additionally had a diagnosis of CHD were better than for patients without CHD. Conclusion: The cross sectional survey suggested the treatment received by some patients with established PAD is substandard. There is considerable potential to increase secondary prevention of CHD in patients with PAD disease in primary care.